Spillover effects in the global copper futures markets: asymmetric multivariate GARCH approaches. Issue 54 (19th November 2020) - Lee, Hyun-Bock; Park, Cheol-Ho
ABSTRACT: This study investigates changes in return and volatility spillovers between the LME/COMEX and the SHFE copper futures markets before and after the global financial crisis and after the introduction of the night trading session (NTS) to the SHFE using asymmetric multivariate GARCH models. The results show that the SHFE has not been stronger to the LME/COMEX in information spillover effects, even though it has grown substantially in terms of trading volume after the crisis. Furthermore, the SHFE does not seem to have a significant influence on international copper futures prices although the Chinese government allowed the NTS to the SHFE.